Retrospective analysis of anterior skull base CSF leaks and endoscopic repairs at Leeds. (3rd July 2016) - Nix, Paul; Tyagi, Atul; Phillips, Nick
Abstract: Objectives : Over the past 10 years, endoscopic endonasal anterior skull base surgery has become established practice. Surgeons carrying out this surgery need to be able to endoscopically repair primary and secondary CSF leaks. A growing number of techniques have been adopted to date. This article highlights one UK institution's experience in the management of anterior skull base leaks, and how surgeons there have identified leak defect types that are difficult to seal and how they have adopted a new way of repairing them, which uses a fat ring.Methods : Seventy-six patients requiring CSF leak repairs were identified form a prospective data base of 240 endoscopic anterior skull base procedures at the General Infirmary at Leeds performed between July 2009 and October 2015.Results : Fifty-one cases have undergone an endoscopic primary repair of a skull base defect following resection of a lesion and, of these, 10 (19%) cases required a secondary repair. This was particularly over the planum sphenoidale area. Twenty-five cases had undergone an endoscopic repair as the primary procedure. This was due to a spontaneous leak in 7 cases, trauma in 3 cases, following craniotomy in 3 cases and following pituitary surgery in 2 cases. The remaining 10 were the secondary repairs referred to above.Conclusions : A number of techniques are effective in CSF repair. Defects over the planum sphenoidale and clivus are associated with the highest recurrence, requiring specific repair techniques. Utilisation of a 5 "F" repair helps to prevent recurrence in high risk defect cases over the optic chiasm. The 5 "F" repair used takes the form of placing intradural Fat and Fascia; next a Fat sealing ring is used, followed by a nasoseptal Flap; finally a supporting fragmentable pack is applied.